SYNERGISTIC COMBINATION OF JAVA PLUM (SYZYGIUMCUMINI(L.) SKEELS) LEAF EXTRACT AND VITAMIN C ON ASPARTATE AMINOTRANSFERASE AND ALANINE AMINOTRANSFERASE LEVELS IN LEAD ACETATE-INDUCED RAT - Ikhsan, M; Rita, Rauza Sukma; Elmatris, Elmatris; Alioes, Yustini; Mahata, Liganda Endo; Almurdi, Almurdi (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Lead (Pb) is a toxic metal that is used to trigger oxidative stress. Oxidative stress causes damage to organs, especially the liver increasing aspartate aminotransferase (AST) and alanine aminotransferase (ALT). This study aims to determine the synergistic effect of antioxidant as Java plum leaf extract and vitamin C together on lead-induced levels of AST and ALT in rats.This type of research is true experimental research with a randomized posttest-only-control group design. The study used 20 male white rats which were divided into 4 groups. The treatment was carried out for 30 days. The examination for AST and ALT levels using the Micro Lab 300 with the Sample Star method. Data analysis was performed by using One-way Anova and Post Hoc-Turkey HSD.In this study, The results were obtained in the form of a decrease in AST and ALT levels in rats that had been induced lead acetate 40 mg/KgBW by administration of Java plum leaf extract dose 75 mg/KgBW and vitamin C dose 35 mg/KgBW as well as the administration of Java plum leaf extract at a dose of 150 mg / KgBB and vitamin C dose of 75 mg / KgBB with significant influence at the lower dose (p=0,01).It can be concluded that administrating of Java plum leaf extract dose 75 mg/KgBB and vitamin C dose 35 mg/KgBB was effective to protect the liver based on the decrease of AST and ALT levels in rats that had been induced lead acetate dose 40 mg/KgBB